THE EFFECT OF PERCEPTION OF EASY AND PERCEPTION OF BENEFITS ON INTEREST IN USING J&T EXPRESS APPLICATION - Reni Safitri; Antoni Ludfi Arifin (Universitas Islam Lamongan, 2022)
This study aims to determine how perceived convenience and perceived benefits affect interest in using the J&T Express application. This study uses quantitative research with variables of perceived convenience, perceived benefits and interest in use. The population in this study are regular package delivery consumers at J&T Express Duren Jaya. The sample used in this study consisted of 120 respondents who were taken using accidental sampling technique. Data was collected using a questionnaire, where each respondent was given 24 statements. The data is then analyzed using validity test techniques, reliability tests, and classical assumption tests. The results of this study indicate that: (1) The effect of perceived ease of use on interest in use gets an interpretation value of 4.26 which means good; (2) The effect of perceived benefits on interest in use gets an interpretation value of 4.21 which means good; (3) The effect of perceived convenience and perceived benefits on interest in use is 60.3%, while 39.7% is influenced by other variables not included in this study.